(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
It is ascertained on base of analyzed empirical material, that such creamery products are products of daily shopping as milk and yogurts and butter, however, buttermilk, moldy cheeses and milky desserts are obtained more rarely definitely.Described behavior of purchasers of creamery products answer model behavior accepted in theory of procedure of purchaser in process of shopping. Purchasers of creamery products choose new products according to model compound process of shopping, during when purchasers of products behaved to practice manner known already.Key factors of shopping of analyzed products taking into account said ascertain, that they decide about shopping of novelty savor most often, advertising and familiar opinion, during when they decide about shopping of product known purchasers most often price and habituation of purchasers. Empirical material described over and results of statistic tests confirm justness of acceptedfoundation about existence of statistic dependence among criterion but form of shopping of creamery product